Reporting negative results to stimulate experimental hydrology: discussion of "The role of experimental work in hydrological sciences – insights from a community survey"*. Issue 8 (11th June 2018) - van Emmerik, Tim; Popp, Andrea; Solcerova, Anna; Müller, Hannes; Hut, Rolf
ABSTRACT: Experimental work in hydrology is in decline. Based on a community survey, Blume et al . showed that the hydrological community associates experimental work with greater risks. One of the main issues with experimental work is the higher chance of negative results (defined here as when the expected or wanted result was not observed despite careful experimental design, planning and execution), resulting in a longer and more difficult publishing process. Reporting on negative results would avoid putting time and resources into repeating experiments that lead to negative results, and give experimental hydrologists the scientific recognition they deserve. With this commentary, we propose four potential solutions to encourage reporting on negative results, which might contribute to a stimulation of experimental hydrology.